ChemInform Abstract: Copper‐Mediated Aerobic Oxidative Cleavage of α, β‐Unsaturated Ketones to 1, 2‐Diketones. Issue 8 (February 2015) - Li, Zheng; Yin, Junjun; Wen, Gong; Li, Tianpeng; Shen, Xiaoli
Abstract The advantages of the method are the use of inexpensive and non‐toxic raw materials, high yields, and simple work‐up procedure.